Modeling of Dissolved Oxygen Profile in a Slurry Reactor - Abid, Mohammad F.; Jabir, Atheel K.; Faiq, Saad A. (Nahrain University College of Engineering Journal, 2011)
A mathematical model for a slurry bioreactor was proposed to describe oxygen utilization rate and concentration profiles along the reactor for reactants and products in the bubbly flow regime. The model consisted of transient differential equations representing mass transfer and kinetics of oxygen, biomass and substrates in the liquid phase. The model was validated by comparing with experimental work of other authors and a good agreement was obtained, theabsolute average error between model and experimental results was 4.3%. The effects of various operating parameters on the concentration profile of oxygen and biomasswere investigated theoretically. The dissolved oxygen concentration was significantly affected by the superficial liquid velocity than that bysuperficial gas velocity. Unsteady state concentration profile of oxygen showed different behaviors gas and liquid.